Enclaves residenciais: morfologia urbana e organização da vizinhança - o caso do Bairro Peixoto em Copacabana - Fernando Schwab Firme (2010)
Since ``Comendador Paulo Felisberto Peixoto da Fonseca did not have any descendants, in 1938 he donated all of his farm land plots to five charities. The donation deeds limited any future construction in that area to be up to three floors high and exclusively for residential purposes. The Bairro Peixoto urbanization, in the Copacabana district, was a late process along with many historical details which contributed to the forging of a differentiated built up area inside that district. The Distrito Federal resorted to its qualified engineers and architects team. The creation of project PA 2990 was up to the town planning engineer José de Oliveira Reis. The project scope was to create a solely residential district, in a mixed sketch, isolated and closed to thru traffic in the last agricultural Copacabana land plot, in the middle of the 40s in the 20th century. The purpose of this work is to establish, by means of a qualitative survey among residents, with sampling segmented by area, by age group and morphological analysis, any relationships between that residential area physical characteristics and the consolidation of neighborhood bonds. The inner plotting which is tangent to the collection of roads seems to have been a right approach for the initial make up of this friendliness and good living together nucleus. However, this concept received a death blow, as individual transportation was chosen by society and the municipality as the main mode of moving around. The Bairro was split in the middle by Rua Figueiredo de Magalhães and it lost its character, becoming a pass thru, which provides an alert for communities like this, where the roads hierarchy should not have been altered under penalty of irreparable fragmentation. It seems that the cultural value of the urban landscape created by the City Planning Commission and its immediate surroundings took the back seat. This region access to the Botafogo district, which was secondary in the road system, received investments which stimulated the individual transportation and changed the district road hierarchy, introducing an arterial road in an area intended for internalization and accessibility, replicating the urban planning and design paradigms of the 20th century